The Digestion Level of Tilapia (Oreochromis niloticus) to Different Combination Feeds - Vini Taru Febriani Prajayati; Otie Dylan Subhakti Hasan; Mugi Mulyono (Journal of Aquaculture and Fish Health, 2021)
Digestibility is food substances from feed consumption that are not excreted into the feces, and the difference between food substances consumed and those excreted in the feces is the amount of food that can be digested. Information about the digestibility value of food is very important as a basis in assessing the quality of food and designing fish feed rations.This research was conducted to determine the level of the feed digestibility in nirvana tilapia (Oreochromis niloticus) feed with a combination of fish meal and maggot flour. This research was conducted at the Hatchery Campus of BAPPL STP Serang, Banten from September-December 2019. This study used a Completely Randomized Design (CRD) with 5 treatments and 3 replications. There were 225 fish used in the testing with an average weight of 0.16 grams. The culture media used was a plastic  container with a size of 60 x 41 x 34 cm. Feeding was carried out for 50 days, with a frequency of twice a day, and the dose of feeding was 3% of the biomass.The results showed the total digestibility parameter of feed, protein digestibility of feed and the highest protein retention in the treatment of 50% of the combination feeds , with the highest total digestibility value of 56.97 ± 3.41 and the lowest of 42.08 ± 0.42, the highest protein digestibility with a value of 87.33 ± 0.95and the lowest of 83.11 ± 1.30 and the highest protein retention with a value of 14.83 ± 0.22and the lowest of 11.69 ± 1.05.